Propuesta de un método basado en Lean Six Sigma enfocado en la cuantificación y mejora para la aplicación del mantenimiento de las blisteras Uhlmann B1330 de Gutis Ltda. - Núñez-Blanco, Fabián Andrés (Instituto Tecnológico de Costa Rica, 2018)
Every maintenance department’s main objective is to guarantee achieving the organization’s goals. A good maintenance management not only offers the assets’ longest life possible, but also needs the required feedback to achieve and maintain the continuous improvement for the productive performance. Lean Six Sigma is a method for continuous process improvement and is based in the DMAIC strategy. It defines the problem, measures the variables that quantify the current performance, analyzes the causes of the problem, improves the aspects that can lessen the problem, and controls the improvements with the performance indicators previously measured. This model can be used to obtain a tool that generates value from the performance indicators (KPI). These numerical values do not provide solutions for themselves, they are the inputs for a methodology that achieves the results. This project tries to show that a quantitative analysis can be the first step to obtain improvements in a maintenance department management. For this research’s purposes, a Lean Six Sigma methodology is presented and developed in the Uhlmann B1330 blister for the Gutis company. The development of the project proves how the indicators support that apparent causes are not always the real causes. This evidences that an analysis is also needed to obtain the results. Therefore, this project’s solutions change from being focused on maintenance plans, and instead, now they focus on improving the maintenance management in SAP. This software is the environment where all the company’s logistics are managed. SAP has some problems with its implementation for the maintenance department. This project tries to solve them and provide an instrument to measure the performance of corporation’s maintenance.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2018.
Keywords: Manufactura; DMAIC; Six Sigma; Indicadores; SAP